The Influence Of Social Media Influencer Marketing (SMIS) Mediated By Credibility On The Purchase Intention Of Kawasaki Ninja ZX-25RR Sport Motorcycles In Indonesia: A Pilot Study - Akbar Maulana, Rizky; Indrawati, Indrawati (Publisher Cv. Inara, 2025)
The rapid rise of social media has shifted marketing strategies toward influencer-driven promotions, particularly for high-involvement products like sport motorcycles. This study explores how different traits of social media influencers affect people’s intention to buy the Kawasaki Ninja ZX-25RR in Indonesia, with credibility playing a mediating role. The research aims to examine the influence of Social Media Influencer Marketing (SMIs) on purchase intention, using credibility as an intervening variable. The model includes three constructs: SMIs (trustworthiness, likability, expertise, and information quality), credibility, and purchase intention. A pilot test was conducted with 30 respondents who were familiar with both the product and the influencer, Harald Arkan. The instrument, consisting of 3 variables and 20 items, was analyzed using SPSS software. The results showed that all items met the validity threshold (CITC > 0.3) and reliability standard (Cronbach’s Alpha > 0.7). Therefore, the instrument is considered valid and reliable for use in the main study.